Analisis Kontribusi Penerimaan Sektor Pariwisata Terhadap Pendapatan Asli Daerah Kabupaten Fakfak - Mesak. E. S. Rahanra (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
Fakfak Regency is one of the autonomous regions located in the territory of West Papua Province. Normatively, this district is still classified as an area rich in potential economic resources. If the potential of these resources can be managed and utilized properly, it will certainly make a positive contribution to the increase of Regional Original Revenue. The Tourism sector is one of the potential and strategic sectors for Regional Original Revenue, because this sector is the main source of Regional Tax and Regional Levy revenue.This study aims to find out the amount of Revenue from the Tourism Sector of Fakfak Regency in the last 5 years, to find out the amount of Contribution of Tourism Sector Revenue to the Original Income of the Fakfak Regency Region, how the theory used in the Development of the Tourism Sector as one of the leading sectors for increasing Regional Original Income. The research method used is a qualitative research method. Based on the results of important research findings, in the last five years the tourism sector has received less attention from the local government of Fakfak district, but the tourism sector's revenue has increased every year.